Narracje zootanatologiczne jako wyznacznik relacji między osobą ludzką i pozaludzką - Poks, Małgorzata (Zoophilologica. Polish Journal of Animal Studies, 2019)
Is animal death grievable and do animals grieve their dead? The answer to these questions depends on the narratives one subscribes to. In the dominant narrative of the Western world, human death is treated with respect and animal death is either invisible or instrumentalized. In this article I am considering the consequences of challenging this narrative from the sites of enunciation that are marginal to modernity and, thus, do not replicate its hyperseparated dualism (Val Plumwood’s phrase). First, I introduce the holistic imaginary of indigenous Americans on the example of Linda Hogan’s novel Solar Storms. Next, on the example of Olga Tokarczuk’s Drive Your Plow over the Bones of the Dead, I move to the perspective of Duszejko – a self-exile from European modernity. Both novels demonstrate that iconographies of death (and life) make a real difference in our relationship to the nonhuman other.